2005
DOI: 10.1080/j.1440-1665.2005.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Stability in Patients with First-Episode Psychosis

Abstract: Affective psychoses and schizophrenia, in line with previous findings, remained stable. Diagnoses of brief psychoses were highly stable as well; this could reflect a non-relapsing course of acute brief psychoses, especially in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…These studies 25,28 averaged with our findings (Table 2) indicated that ICD-10 schizophrenia was a particularly stable initial diagnosis (92.2±9.2%), mania with psychotic symptoms similarly stable (90.8±8.4%), delusional disorder and severe depressive episode with psychotic features less stable (75.4±21.2%), ATPD moderately unstable (63.7±32.6%), and the pool of unspecified acute psychoses even less stable (40.1±24.1% of cases remaining stable for at least one year). Compared with our findings of 100% longitudinal diagnostic stability among initial ICD-10 schizoaffective cases (Table 2), one comparable study found that only 20% of cases initially considered schizoaffective (2.9%) remained so at 36 months, 25 and the other did not identify any subject as schizoaffective at baseline or at 12-months.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…These studies 25,28 averaged with our findings (Table 2) indicated that ICD-10 schizophrenia was a particularly stable initial diagnosis (92.2±9.2%), mania with psychotic symptoms similarly stable (90.8±8.4%), delusional disorder and severe depressive episode with psychotic features less stable (75.4±21.2%), ATPD moderately unstable (63.7±32.6%), and the pool of unspecified acute psychoses even less stable (40.1±24.1% of cases remaining stable for at least one year). Compared with our findings of 100% longitudinal diagnostic stability among initial ICD-10 schizoaffective cases (Table 2), one comparable study found that only 20% of cases initially considered schizoaffective (2.9%) remained so at 36 months, 25 and the other did not identify any subject as schizoaffective at baseline or at 12-months.…”
Section: Discussionmentioning
confidence: 97%
“…38 Accordingly, ICD-10 diagnoses of ATPD, particularly the APPD subtypes, may be somewhat more stable, and potentially more reliable and valid constructs than DSM-IV schizophreniform and brief psychotic disorder. Several studies 21,25,39,41,43,44 investigated the incidence, characteristics, and diagnostic stability of ICD-10 acute, transient psychoses, alone or within the broad range of first-episode functional psychoses, generally finding low to moderate overall stability rates (34.4%–57.9%), though relatively high positive predictive power was found among such diagnoses in developing countries (64.4%–73.3%), 28,40,42 particularly for the APPD subtypes. 40 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to schizophreniform disorder, DSM-IV brief psychotic disorder was a moderately stable category since only 38.9% later changed, usually to BPD or psychosis-NOS. Unlike schizophreniform disorder, brief psychoses often are relatively acute and time-limited, may be episodic but rarely follow a chronic course, and often appear in relatively well-functioning women 11,12,15,17,18,24,26,37. Brief psychosis,4 as well as “acute and transient psychoses” of ICD-10,5 may be more valid constructs than schizophreniform disorder, and appears to be associated with a more episodic-favorable course.…”
Section: Discussionmentioning
confidence: 99%